Cognitive Lexicography. A New Approach to Lexicography Making Use of Cognitive Semantics. - Ostermann, Carolin (Walter de Gruyter, 2015)
Cognitive Lexicography demonstrates how insights gained in cognitive semantic research can be applied to different parts of the traditional English monolingual dictionary entry. Three features are developed, and cover the example section, the definitions, and the microstructure of polysemous entries, each for a different set of lexemes. Dictionary analyses related to all features and user studies on two of the features complement the approach.
Keywords: Lexikographie; Kognitive Linguistik